2013
DOI: 10.3389/fimmu.2013.00428
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem and Progenitor Cells in Inflammation and Allergy

Abstract: Hematopoietic stem and progenitor cells contribute to allergic inflammation. Pro-inflammatory cytokines that are generated following allergen challenge can impact the differentiation of hematopoietic progenitor cells leading to increased production of effector cells such as eosinophils and basophils, which are key cells involved in the pathogenesis of allergic airway inflammation. Homing of stem cells to the lungs is associated with inflammatory and remodeling changes in asthmatics. Factors that modulate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…HSPCs respond to inflammation with emergency hematopoiesis, a process that replaces immune effectors that are destroyed, exhausted, or otherwise occupied with clearance of inflammatory stimuli . In a more nuanced role, HSPCs can enhance or diminish the highly educated adaptive immune system through MDSC‐like immune suppression or myeloid antigen‐presenting cell‐like immune activation . In each of these functions, HSPCs can enable or prevent infections, autoimmunity, cancers, and even modulate surgical site healing responses .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSPCs respond to inflammation with emergency hematopoiesis, a process that replaces immune effectors that are destroyed, exhausted, or otherwise occupied with clearance of inflammatory stimuli . In a more nuanced role, HSPCs can enhance or diminish the highly educated adaptive immune system through MDSC‐like immune suppression or myeloid antigen‐presenting cell‐like immune activation . In each of these functions, HSPCs can enable or prevent infections, autoimmunity, cancers, and even modulate surgical site healing responses .…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic stem and progenitor cells (HSPCs) at various stages of multipotency and lineagecommitment have been implicated as key modulators of immunity [1]. Namely, it has been suggested that HSPCs can regulate cancer progression [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], drive autoimmunity [18][19][20], and regulate infections and inflammation [1,[20][21][22][23][24][25][26][27][28][29][30]. In each of these disease settings, multiple reports have described HSPC-mediated immune-suppressive and stimulatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…After an experimental infection with the mentioned parasite, the number of myeloid progenitors in the whole liver was equivalent to half of their content in the femur [22]. Also, myeloid progenitors home to sites of allergic reaction and it is proposed that stimulation with local cytokine milieux infl uence their differentiatiation in situ to eosinophiles and basophils [18]. Although all initial studies leading to the discovery of bone marrow HSPCs have been done in canines, no studies on dogs, or other large animals, have been done concerning the role of myeloid progenitors in different pathologies.…”
Section: Mobilization and Homing Of Stem And Progenitor Cellsmentioning
confidence: 98%
“…The site of their homing without any pathological event is not so clear, but current evidence suggests that HSPCs traffi c for several days through various extramedullary tissues, draining through the lymphatic circulation to reach again the blood and bone marrow [17]. Much more is known about HPSC mobilization as a consequence of different types of stress and infl ammation that lead to HPSC recruitment to the sites of tissue injury [18].…”
Section: Mobilization and Homing Of Stem And Progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation